2016
DOI: 10.1016/j.ssmph.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

“ By slapping their laps, the patient will know that you truly care for her ”: A qualitative study on social norms and acceptability of the mistreatment of women during childbirth in Abuja, Nigeria

Abstract: BackgroundMany women experience mistreatment during childbirth in health facilities across the world. However, limited evidence exists on how social norms and attitudes of both women and providers influence mistreatment during childbirth. Contextually-specific evidence is needed to understand how normative factors affect how women are treated. This paper explores the acceptability of four scenarios of mistreatment during childbirth.MethodsTwo facilities were identified in Abuja, Nigeria. Qualitative methods (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
118
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 27 publications
11
118
0
1
Order By: Relevance
“…This explanation parallels other literature in the field [27, 28, 49]; however mistreatment cannot be blamed solely on the health system. Another publication resulting from this study explored social norms and acceptability of mistreatment during childbirth in Nigeria, and found that both women and healthcare providers considered physical and verbal abuse as acceptable and appropriate measures to gain compliance from the woman and ensure a good outcome for the baby [50]. Furthermore, in Nigeria, women and their families are unable to express their satisfaction or dissatisfaction with services rendered, thus hindering the ability to engage with users and improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation parallels other literature in the field [27, 28, 49]; however mistreatment cannot be blamed solely on the health system. Another publication resulting from this study explored social norms and acceptability of mistreatment during childbirth in Nigeria, and found that both women and healthcare providers considered physical and verbal abuse as acceptable and appropriate measures to gain compliance from the woman and ensure a good outcome for the baby [50]. Furthermore, in Nigeria, women and their families are unable to express their satisfaction or dissatisfaction with services rendered, thus hindering the ability to engage with users and improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…This manifested through the treatment of birth as a medical event only, thus disregarding critical psychosocial elements of care . Bohren et al . and Jewkes and Penn‐Kekana echo this sentiment and draw parallels between structural gender inequalities, social pressures to denounce abusive acts toward women, and justifications for mistreatment during childbirth and violence against women more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…For example this may include slapping, pinching, verbal abuse, lack of privacy and discrimination [3]. In recent years, evidence from several sub-Saharan African countries, including Tanzania [4, 5], Kenya [6, 7], Nigeria [8] and Ghana [9–11], suggests that mistreatment during childbirth may be a common occurrence, and may be exacerbated by certain characteristics of the woman, including age and HIV status. This work has been groundbreaking to better understand women’s experiences of mistreatment during childbirth, as well as efforts to measure mistreatment that does occur, through observations of labor and childbirth, and follow-up surveys with women.…”
Section: Introductionmentioning
confidence: 99%